The Effectiveness of The Polygraph Instrument (Lie Detector) As Evidance In Court - Fersa, Hawwa Saqinah (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
Polygraph is a computer technology that is capable of interpreting fraud up to 98% through physiological data such as changes in skin moisture due to anxiety, blood pressure, respiratory frequency and pulse frequency. The National Police Chief's Regulation (Perkap) Number 10 of 2009 Article 9 Paragraph (2) Letter A stipulated that the use of a polygraph as evidence in court will provide assistance to the judge in making a decision although the polygraph cannot be used as evidence because it does not meet the required standards. The purpose of this research is how to study the law on the use of polygraph equipment as valid evidence in court as written in the ITE Law Number 19 of 2016 concerning amendments to the UU ITE Number 11 of 2008. The research uses normative law as a research method and uses primary, secondary and data. tertiary. Research has found that a polygraph cannot be used as evidence, but if supported by expert opinion it can be used as valid supporting evidence in court.